ChemInform Abstract: Rh(III)‐Catalyzed Dehydrogenative Alkylation of (Hetero)arenes with Allylic Alcohols, Allowing Aldol Condensation to Indenes. Issue 43 (7th October 2013) - Shi, Zhuangzhi; Boultadakis‐Arapinis, Melissa; Glorius, Frank
Abstract The dehydrogenative cross‐coupling of indoles (I) and 2‐phenylpyridine (IV) with allylic alcohols (II) affords β‐aryl carbonyl compounds as sole products.